2015
DOI: 10.4018/ijcallt.2015100103
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Flipped Classrooms on English Composition Writing in an EFL Environment

Abstract: The authors discuss the empirical results of a study comparing two English composition courses conducted with Japanese university students. One course was taught in a traditional way and the other using the flipped method. The results showed that those studying under the flipped method spent a significantly higher number of hours preparing for class (t(20) = 2.67, p = .014, d = 1.14) and produced a significantly higher number of words in compositions written in the posttest (t(10) = 3.37, p = .007, d = 1.44). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 26 publications
9
28
0
1
Order By: Relevance
“…On the other hand, students' perception of the flipped learning approach does not necessarily correlate with their academic performance. Moraros, Islam, Yu, Banow, and Schindelka (2015) reported that the majority of the participants in their study (67 Public Health students) found this approach to be effective, even though it did not enhance their grades in the course (as cited in Leis et al (2015)). Moreover, Bishop and Verleger (2013) provide a comprehensive survey of twenty-four, prior and ongoing studies related to flipped classrooms in 2012.…”
Section: Flipped Classrooms: Overcoming Common Hurdlesmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, students' perception of the flipped learning approach does not necessarily correlate with their academic performance. Moraros, Islam, Yu, Banow, and Schindelka (2015) reported that the majority of the participants in their study (67 Public Health students) found this approach to be effective, even though it did not enhance their grades in the course (as cited in Leis et al (2015)). Moreover, Bishop and Verleger (2013) provide a comprehensive survey of twenty-four, prior and ongoing studies related to flipped classrooms in 2012.…”
Section: Flipped Classrooms: Overcoming Common Hurdlesmentioning
confidence: 99%
“…In addition, since this learning approach is techno-driven, some educators may not welcome its application as it requires technological knowledge, such as of educational media programs and video recordings (Sams, 2011). In his PhD thesis, Strayer (2007) suggested that teachers should decrease the array of tasks for learning to increase students' satisfaction (as cited in Leis et al (2015)). Accordingly, teachers need to keep in mind that the ultimate goal is not to drown students with a lot of assignments, and as a result, increase their anxiety levels, but to facilitate and improve the quality of their learning.…”
Section: Challenges Of Applying Flipped Classrooms Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that students in the experimental group outperformed students in the control group. On the same track, Leis et al (2015) conducted a study comparing two English composition courses used with Japanese university students. One course was taught in a traditional way and the other using the flipped classroom.…”
Section: The Effect Of Flipped Classrooms On Students' Performancementioning
confidence: 99%